Space of Functions with Some Generalization of Bounded Variation in the Sense of de La Vallée Poussin. (4th June 2015) - Castillo, René Erlín; Rafeiro, Humberto; Trousselot, Eduard
Abstract : We introduce a function space with some generalization of bounded variation in the sense of de la Vallée Poussin and study some of its properties, like embeddings and decompositions, among others.